Women in Management: a Developing Presence - Dasgupta, Pritha; Phadke, Suniti (Ushus Journal of Business Management, 2021)
Women in management, today are performing important tasks but very few have advanced to the top echelons of corporate power. Work place policies have adjusted somewhat towards accommodating women managers, but they have not produced a situation that most observors would label as equal for women and men. Yet avenues for positive changes do exist, Women have to recognise and develop their inherent qualities and innate skills to satisfy the future knowledge world. Self empowerment appears to be the answer for women managers.